The Influence of Principals' Leadership and Work Motivation on Teacher Performance in Middle Schools - Tanjaya, Mikael Abdisa; Arafat, Yasir; Suherman, Suherman (research, training and philanthropy institution Natural Aceh, 2024)
This study aims to identify and describe (1) the influence of the principal's leadership on teacher performance in junior high schools in Muara Telang District, Banyuasin Regency; (2) the influence of work motivation on teacher performance in junior high schools in Muara Telang District, Banyuasin Regency; (3) the influence of the principal's leadership and work motivation together on teacher performance at SMP Muara Telang District, Banyuasin Regency. This research is quantitative. This research was conducted at Muara Telang District Middle School, Banyuasin Regency, with 53 teachers as respondents. The data in this research was collected by distributing questionnaires to respondents. Data collection techniques use questionnaires and documentation. Test the prerequisites for analysis using the normality test, linearity test, and multicollinearity test, as well as the simple linear regression technique t-test and multiple linear tests using the F test with the help of the Product and Service Solution (SPSS) Statistics Program version 25. The results of this research show that (1) there is an influence of the principal's leadership on teacher performance at SMP Muara Telang District, Banyuasin Regency; (2) there is an influence of work motivation on teacher performance in junior high schools in Muara Telang District, Banyuasin Regency; (3) there is an influence of the principal's leadership and work motivation together on teacher performance at SMP Muara Telang District, Banyuasin Regency.